The role of IoT in achieving a smart Hajj Management - Jebreel Alarishee; Sara Alqahtani (Cybrarians Journal, 2019)
ICTs is evolving so rapidly that their products have become essential for providing solutions to all our problems and daily life situations. The emergence of the IoT, which is one of the new ICT domains, has led to major changes in the physical world surrounding us, allowing for the integration of all the things we use every day into the internet information world. This research provides a solution for monitoring and controlling people, public vehicles and service facilities in Hajj areas. It integrates IoT architecture with many other technologies in order to provide a capability of monitoring these three components by Hajj authorities, so that they would be able to plan for the Hajj season and make appropriate real time decisions of what might happen on the ground. The suggested system collects data of mobile phones, carried by pilgrims, through Wi-Fi, Bluetooth, and GPS sensors embedded in them. It also, at pre-defined locations, monitors and collects data from the RFID equipped bracelets they wear. At the same time, it collects public transport vehicles positioning data and service facilities static data, from the active RFID chips mounted on them. The data collected will be stored on IoT cloud and integrated with data from other sources, enabling for being monitored and analyzed by Hajj authority personnel. They would be able, accordingly, to send messages and instructions to pilgrims and field administrative personnel to handle crisis situations. The suggested solution is further enhanced by integrating the collected IoT – based data with local mobile networks data, so that a more accurate and comprehensive picture of the movement of crowds of pilgrims can be obtained.